THE URGENCY AND FUNCTION OF LEARNING ARABIC IN EDUCATIONAL INSTITUTIONS - Amar, Fathur Rusydi (PT. Antis International Publisher, 2025)
Objective: This study aims to determine the urgency and function of Arabic language learning in educational institutions, emphasizing its importance in developing religious understanding, intercultural connections, and opportunities in various areas of life. Method: The research uses a qualitative descriptive method with a library research approach, which means it is conducted in a library or through library resources such as books, journals, databases, and other information sources to support or develop specific arguments or research. Result: The findings show that Arabic has significant urgency in educational institutions for several reasons, including its role as the language of the Quran, its importance in religious education, classical Arabic literature, international communication, higher education, intelligence enhancement, employment opportunities, and cultural diversity. Arabic also serves multiple functions in education, especially within the context of the Arab world and Islamic studies, such as facilitating Quranic interpretation, supporting Islamic scholarship, promoting international relations, preserving literary heritage, enhancing cognitive skills, expanding job opportunities, fostering cultural understanding, and maintaining cultural identity. Novelty: This study highlights a comprehensive view of the dual role of Arabic—as both a medium of religious and intellectual enrichment and as a bridge to global communication and cultural preservation—underscoring its irreplaceable value in modern educational contexts.